Method for detecting core-shell structure of sintered neodymium-iron-boron permanent magnet alloy subjected to tb diffusion treatment
By employing specific etchant treatments and metallographic testing methods, the problem of not being able to clearly observe the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys in existing technologies has been solved, enabling clear observation of the core-shell structure and optimization of diffusion parameters.
Patent Information
- Application Number
- CN202410858362.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-06-28
AI Technical Summary
Existing technologies lack effective detection methods to observe the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, which affects the optimization of diffusion process parameters.
By employing specific etching methods, including a combination of nitric acid, hydrochloric acid, and phosphoric acid solutions, combined with hot mounting, grinding, and polishing steps, the metallographic grain boundaries and shell structure of the alloy are clearly revealed.
This study enabled clear observation of the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, helping to determine the optimal diffusion parameters and improving detection efficiency and accuracy.
Smart Images

Figure CN118883192B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of alloy testing technology, and in particular to a method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys. Background Technology
[0002] Neodymium iron boron permanent magnets are tetragonal crystals formed from neodymium, iron, and boron, Nd2FE 14 As the sintered main body, Nd₂Fe₂ is the only hard magnetic term and the main source of magnetism. Due to its structural characteristics, it can exhibit high magnetic properties at room temperature and is widely used in the automotive industry. In automotive motors and generators, due to its high energy product and good permeability, this magnet can increase speed and power density while reducing the overall weight of the engine and fuel consumption. Furthermore, NdFe₂ magnets play a crucial role in the motors and drive systems of electric and hybrid vehicles, providing efficient energy and high power output. They are also used in components such as sensors and brakes in automotive braking systems. Their good magnetic force and permeability also contribute to improving braking performance and sensitivity, thereby enhancing vehicle safety. Research has found that for this material, Nd₂Fe₂... 14 B is used as the sintering body, and Tb2Fe is used. 14 After replacing part B, the magnetocrystalline field is three times larger, which can effectively improve coercivity. (Tb2Fe) 14 B forms a shell structure through a diffusion process, effectively suppressing phase domain nucleation and improving coercivity. The finer the grain size, the more numerous and uniform the shell structures that can be formed at the grain boundaries, resulting in higher coercivity and thus optimal magnetic properties of the magnet. Therefore, observation of the core-shell structure is of significant reference value for determining the optimal grain boundary diffusion process parameters. However, there is currently no good method for detecting its core-shell structure. Summary of the Invention
[0003] This application provides a method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, which can effectively detect the core-shell structure of the alloy and thus help determine the optimal diffusion parameters.
[0004] This application provides a method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, the method comprising:
[0005] The alloy to be tested is pretreated to remove its magnetism and clean it, resulting in a pretreated sample.
[0006] The pretreated alloy was hot-mounted to obtain a mounted sample;
[0007] The inlaid sample is ground and polished to obtain a glossy sample;
[0008] Prepare a corrosive agent, wherein the corrosive agent includes nitric acid solution, hydrochloric acid solution and phosphoric acid solution;
[0009] The glossy sample was etched using the etchant, and then tested.
[0010] As an optional implementation, the corrosive agent comprises, by volume percentage: 4%–5% nitric acid solution, 1%–2% hydrochloric acid solution, and 1.5%–2.5% phosphoric acid solution, with the balance being water.
[0011] As an optional embodiment, the nitric acid solution has a mass percentage concentration of 65% to 69%; and / or
[0012] The hydrochloric acid solution has a mass percentage concentration of 36% to 38%; and / or
[0013] The phosphoric acid solution has a mass percentage concentration of 83% to 90%.
[0014] As an optional implementation, the corrosion temperature is 22°C to 28°C.
[0015] As an optional implementation, the etching time is 15 to 20 seconds.
[0016] As an optional implementation, the composition of the alloy to be tested, by mole fraction, includes: 29%–32.5% neodymium; and / or
[0017] The composition of the alloy to be tested, by mole fraction, includes: 63.95%–68.65% iron; and / or
[0018] The alloy to be tested, by mole fraction, comprises: 1.1% to 1.2% boron; and / or
[0019] The composition of the alloy to be tested, by mole fraction, includes: 0.6% to 8% dysprosium; and / or
[0020] The composition of the alloy to be tested, by mole fraction, includes: 0.3% to 0.5% niobium; and / or
[0021] The composition of the alloy to be tested, by mole fraction, includes: 0.3% to 0.5% aluminum;
[0022] The composition of the alloy to be tested, by mole fraction, includes: 0.05% to 0.15% copper; and / or
[0023] The composition of the alloy to be tested, expressed as a mole fraction, includes a Tb content of 1% to 2%.
[0024] As an optional implementation, the pretreatment includes demagnetization and cleaning.
[0025] As an optional implementation, the heat-mounting is performed using HM1 phenolic resin.
[0026] As an optional implementation, the grinding sample includes coarse grinding and fine grinding.
[0027] As an optional implementation, the polishing sandpaper is at least 800 grit.
[0028] The technical solutions provided in this application have the following advantages compared with the prior art:
[0029] The method provided in this application, through treatment with a specific etchant, results in clear metallographic grain boundaries in the Tb diffusion-treated sintered NdFeB permanent magnet alloy, and the (Nd,Tb)₂Fe formed by the diffusion process can be clearly observed. 14 The B-shell structure can help determine the optimal diffusion parameters. Attached Figure Description
[0030] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0031] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0032] Figure 1 A flowchart illustrating the method provided in the embodiments of this application;
[0033] Figure 2 This is a diagram of the detection results provided in Embodiment 1 of this application;
[0034] Figure 3 This is a diagram of the test results provided in Comparative Example 1 of this application;
[0035] Figure 4 This is a diagram of the test results provided in Comparative Example 2 of this application;
[0036] Figure 5 The image shows the test results provided for Comparative Example 3 of this application. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0038] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0039] like Figure 1 As shown in the figure, this application provides a method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys. The specific process is as follows:
[0040] The alloy to be tested is pretreated, including demagnetization and cleaning. Demagnetization makes it easier to polish the sample later, and cleaning removes dirt and oil from the sample surface.
[0041] In some embodiments, the composition of the alloy to be tested, by mole fraction, includes: 29%–32.5% neodymium (rare earth metal), 63.95%–68.65% iron (metallic element), 1.1%–1.2% boron (non-metallic element), 0.6%–8% dysprosium, 0.3%–0.5% niobium, 0.3%–0.5% aluminum, 0.05%–0.15% copper, etc., and the content of the diffusion element Tb is 1%–2%.
[0042] Secondly, the sample is hot-mounted using HM1 phenolic resin. The resin powder is added to more than 1 / 3 of the volume of the cavity mold in the mounting machine. The mounting machine temperature is set to 170℃, the heating time is 800s, the holding time is 200s, and the cavity pressure is 8000N.
[0043] Then, the sample is ground and polished. The sample is polished after passing through at least 800-grit sandpaper; preferably, the sample is polished after passing through at least 1200-grit sandpaper.
[0044] Specifically, the grinding sample mainly includes coarse grinding and fine grinding.
[0045] Rough grinding is generally performed on a belt grinder with a 320-grit mesh and a rotation speed of 800 rpm. Abrasive particles fixed on the belt scrape across the sample surface under high stress, removing material by generating abrasive debris. This leaves grinding marks on the sample surface and forms a deformed damage layer of a certain depth, removing the sample's edges and burrs. The coarseness of the abrasive grains has a certain impact on the sample surface roughness and grinding efficiency. During rough grinding, the water valve should be continuously turned on for cooling to prevent changes in the microstructure.
[0046] Fine grinding, or polishing, prepares the sample for the next polishing step. This is because although the sample surface is smooth after coarse grinding, deep grinding marks and surface deformation layers remain, requiring gradual reduction through grinding with metallographic abrasive paper ranging from coarse to fine. Metallographic abrasive paper is an important material for polishing metallographic samples, and silicon carbide is generally used as the abrasive. Polishing is performed sequentially with 120-grit, 320-grit, 800-grit, and 1200-grit metallographic abrasive paper. Each time the abrasive paper is changed, the sample should be rotated 90 degrees to ensure complete removal of the previous grinding marks. Before polishing, a layer of glycerin should be applied to the abrasive paper to prevent abrasive particles from embedding into the sample surface.
[0047] Polishing the sample aims to remove the fine scratches and surface deformation layer left by fine grinding on the metallographic surface, resulting in a smooth, scratch-free mirror finish. Metallographic sample polishing is divided into coarse polishing and fine polishing. The coarse polishing fabric plays a crucial role in polishing the metallographic sample, relying on the friction between the fabric and the polishing surface to achieve a bright finish. During polishing, the interfiber spaces of the fabric can store and support polishing powder, thus producing a grinding effect. Commonly used coarse polishing fabrics include canvas, using a 9μm diamond suspension polishing agent. Fine polishing fabrics include velvet or silk, using 3μm and 1μm diamond suspension polishing agents sequentially. During polishing, the pressure applied to the sample should be even, starting with heavier pressure and gradually decreasing, with the polishing disc set to 300 rpm. In the initial stage of polishing, the direction of the scratches on the sample should be perpendicular to the direction of the polishing disc rotation to facilitate faster scratch removal. In the later stages of polishing, the sample should be rotated slowly to obtain a bright and smooth surface, while preventing inclusions and hard phases from causing a trailing phenomenon.
[0048] Next, prepare the etchant. The etchant needs to be freshly prepared. Add a certain amount of nitric acid, hydrochloric acid, and phosphoric acid to deionized water to make a etchant solution. The volume fractions of nitric acid, hydrochloric acid, and phosphoric acid are 4%–5%, 1%–2%, and 1.5%–2.5%, respectively, with the remainder being deionized water. When preparing the solution, add nitric acid first, then hydrochloric acid, and finally phosphoric acid and deionized water. Stir well with a glass rod. The mass percentage concentration of nitric acid is 65–69%, the mass percentage concentration of hydrochloric acid is 36–38%, and the mass percentage concentration of phosphoric acid is 83–90%.
[0049] Specifically, the etchant needs to be freshly prepared. If the etchant is left for a long time after preparation, the components in the etchant will evaporate, the concentration of the etchant will decrease, resulting in poor subsequent etching effect, which will cause problems for the subsequent grain boundary manifestation of neodymium magnet alloy metallography.
[0050] Next, the sample is etched by placing a petri dish containing the etching solution in a constant temperature water bath at 22-28℃. The metallographic sample treated in the above steps is then placed into the petri dish and immersed in the etching solution for 15-20 seconds. After the etching process is complete, the sample is removed, rinsed with anhydrous ethanol, and then dried with cold air.
[0051] Finally, the metallographic structure of the Tb diffusion-treated sintered NdFeB permanent magnet alloy was observed and photographed under a scanning electron microscope.
[0052] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to national standards. If there is no corresponding national standard, then general international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0053] Example 1
[0054] A method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, the process of which is as follows:
[0055] a. The Tb diffusion-treated sintered NdFeB permanent magnet alloy sample was subjected to demagnetization, pre-cleaning, hot mounting, mechanical grinding and mechanical polishing in sequence, and then rinsed with water and dried with cold air to obtain metallographic sample.
[0056] The specific process of hot mounting is as follows: HM1 phenolic resin is used for hot mounting, and the resin powder is added to more than 1 / 3 of the volume of the cavity mold in the mounting machine. The temperature of the mounting machine is set to 170℃, the heating time is 800s, the holding time is 200s, and the cavity pressure is 8000N.
[0057] Mechanical grinding includes coarse grinding and fine grinding. Coarse grinding is performed on a 320-grit belt grinder at 800 rpm. Abrasive particles fixed on the belt scrape across the sample surface with high stress, removing material in the form of abrasive debris. This leaves grinding marks on the sample surface and forms a deformation damage layer of a certain depth, removing the sharp edges and burrs of the sample. Fine grinding uses silicon carbide abrasive. The sample is polished sequentially with 120-grit, 320-grit, 800-grit, and 1200-grit metallographic sandpaper. Each time the sandpaper is changed, the sample should be rotated 90 degrees to ensure complete removal of the grinding marks from the previous pass. Before grinding, a layer of glycerin is applied to the sandpaper to prevent abrasive particles from embedding into the sample surface.
[0058] Mechanical polishing includes rough polishing and fine polishing. For rough polishing, use canvas and a 9μm diamond suspension polishing agent. For fine polishing, use velvet and apply 3μm and 1μm diamond suspension polishing agents sequentially. During polishing, apply even pressure to the sample, starting with heavier pressure and gradually decreasing it. Set the polishing disc speed to 300 rpm. In the initial stage of polishing, the direction of the abrasion marks on the sample should be perpendicular to the direction of the polishing disc rotation to facilitate faster removal of the abrasion marks. In the later stages of polishing, rotate the sample slowly.
[0059] b. Add 4.5 mL of nitric acid, 1.5 mL of hydrochloric acid, 2 mL of phosphoric acid, and 92 mL of deionized water to a container in sequence to obtain a metallographic etchant. The mass percentage concentration of the nitric acid used is 65-69%, the mass percentage concentration of the hydrochloric acid is 36-38%, and the mass percentage concentration of the phosphoric acid is 83-90%.
[0060] c. Pour the metallographic etchant into a petri dish, place the petri dish in a 25°C constant temperature water bath, immerse the metallographic sample obtained in step a in the metallographic etchant, and etch for 18 seconds. After etching, rinse the sample with anhydrous ethanol and dry it with cold air. Observe the metallographic structure of the Tb diffusion-treated sintered NdFeB permanent magnet alloy under a scanning electron microscope. The morphology after etching is as follows. Figure 2 As shown.
[0061] Comparative Example 1
[0062] A method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, the process of which is as follows:
[0063] a. The Tb diffusion-treated sintered NdFeB permanent magnet alloy sample was subjected to demagnetization, pre-cleaning, hot mounting, mechanical grinding and mechanical polishing in sequence, and then rinsed with water and dried with cold air to obtain metallographic sample.
[0064] The specific process of hot mounting is as follows: HM1 phenolic resin is used for hot mounting, and the resin powder is added to more than 1 / 3 of the volume of the cavity mold in the mounting machine. The temperature of the mounting machine is set to 170℃, the heating time is 800s, the holding time is 200s, and the cavity pressure is 8000N.
[0065] Mechanical grinding includes coarse grinding and fine grinding. Coarse grinding is performed on a 320-grit belt grinder at 800 rpm. Abrasive particles fixed on the belt scrape across the sample surface with high stress, removing material in the form of abrasive debris. This leaves grinding marks on the sample surface and forms a deformation damage layer of a certain depth, removing the sharp edges and burrs of the sample. Fine grinding uses silicon carbide abrasive. The sample is polished sequentially with 120-grit, 320-grit, 800-grit, and 1200-grit metallographic sandpaper. Each time the sandpaper is changed, the sample should be rotated 90 degrees to ensure complete removal of the grinding marks from the previous pass. Before grinding, a layer of glycerin is applied to the sandpaper to prevent abrasive particles from embedding into the sample surface.
[0066] Mechanical polishing includes rough polishing and fine polishing. For rough polishing, use canvas and a 9μm diamond suspension polishing agent. For fine polishing, use velvet and apply 3μm and 1μm diamond suspension polishing agents sequentially. During polishing, apply even pressure to the sample, starting with heavier pressure and gradually decreasing it. Set the polishing disc speed to 300 rpm. In the initial stage of polishing, the direction of the abrasion marks on the sample should be perpendicular to the direction of the polishing disc rotation to facilitate faster removal of the abrasion marks. In the later stages of polishing, rotate the sample slowly.
[0067] b. Add 5.5 mL of nitric acid, 2.5 mL of hydrochloric acid, and 92 mL of deionized water to a container in sequence to obtain a metallographic etchant. The mass percentage concentration of the nitric acid and hydrochloric acid used is the same as in Example 1.
[0068] c. Pour the metallographic etchant into a petri dish, place the petri dish in a 25°C constant temperature water bath, immerse the metallographic sample obtained in step a in the metallographic etchant, and etch for 18 seconds. After etching, rinse the sample with anhydrous ethanol and dry it with cold air. Observe the metallographic structure of the Tb diffusion-treated sintered NdFeB permanent magnet alloy under a scanning electron microscope. The morphology after etching is as follows. Figure 3 As shown.
[0069] Comparative Example 2
[0070] A method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, the process of which is as follows:
[0071] a. The Tb diffusion-treated sintered NdFeB permanent magnet alloy sample was subjected to demagnetization, pre-cleaning, hot mounting, mechanical grinding and mechanical polishing in sequence, and then rinsed with water and dried with cold air to obtain metallographic sample.
[0072] The specific process of hot mounting is as follows: HM1 phenolic resin is used for hot mounting, and the resin powder is added to more than 1 / 3 of the volume of the cavity mold in the mounting machine. The temperature of the mounting machine is set to 170℃, the heating time is 800s, the holding time is 200s, and the cavity pressure is 8000N.
[0073] Mechanical grinding includes coarse grinding and fine grinding. Coarse grinding is performed on a 320-grit belt grinder at 800 rpm. Abrasive particles fixed on the belt scrape across the sample surface with high stress, removing material in the form of abrasive debris. This leaves grinding marks on the sample surface and forms a deformation damage layer of a certain depth, removing the sharp edges and burrs of the sample. Fine grinding uses silicon carbide abrasive. The sample is polished sequentially with 120-grit, 320-grit, 800-grit, and 1200-grit metallographic sandpaper. Each time the sandpaper is changed, the sample should be rotated 90 degrees to ensure complete removal of the grinding marks from the previous pass. Before grinding, a layer of glycerin is applied to the sandpaper to prevent abrasive particles from embedding into the sample surface.
[0074] Mechanical polishing includes rough polishing and fine polishing. For rough polishing, use canvas and a 9μm diamond suspension polishing agent. For fine polishing, use velvet and apply 3μm and 1μm diamond suspension polishing agents sequentially. During polishing, apply even pressure to the sample, starting with heavier pressure and gradually decreasing it. Set the polishing disc speed to 300 rpm. In the initial stage of polishing, the direction of the abrasion marks on the sample should be perpendicular to the direction of the polishing disc rotation to facilitate faster removal of the abrasion marks. In the later stages of polishing, rotate the sample slowly.
[0075] b. Add 5.5 mL of nitric acid, 2.5 mL of phosphoric acid, and 92 mL of deionized water to a container in sequence to obtain a metallographic etchant. The mass percentage concentration of nitric acid and hydrochloric acid used is the same as in Example 1.
[0076] c. Pour the metallographic etchant into a petri dish, place the petri dish in a 25°C constant temperature water bath, immerse the metallographic sample obtained in step a in the metallographic etchant, and etch for 18 seconds. After etching, rinse the sample with anhydrous ethanol and dry it with cold air. Observe the metallographic structure of the Tb diffusion-treated sintered NdFeB permanent magnet alloy under a scanning electron microscope. The morphology after etching is as follows. Figure 4 As shown.
[0077] Comparative Example 3
[0078] a. The Tb diffusion-treated sintered NdFeB permanent magnet alloy sample was subjected to demagnetization, pre-cleaning, hot mounting, mechanical grinding and mechanical polishing in sequence, and then rinsed with water and dried with cold air to obtain metallographic sample.
[0079] The specific process of hot mounting is as follows: HM1 phenolic resin is used for hot mounting, and the resin powder is added to more than 1 / 3 of the volume of the cavity mold in the mounting machine. The temperature of the mounting machine is set to 170℃, the heating time is 800s, the holding time is 200s, and the cavity pressure is 8000N.
[0080] Mechanical grinding includes coarse grinding and fine grinding. Coarse grinding is performed on a 320-grit belt grinder at 800 rpm. Abrasive particles fixed on the belt scrape across the sample surface with high stress, removing material in the form of abrasive debris. This leaves grinding marks on the sample surface and forms a deformation damage layer of a certain depth, removing the sharp edges and burrs of the sample. Fine grinding uses silicon carbide abrasive. The sample is polished sequentially with 120-grit, 320-grit, 800-grit, and 1200-grit metallographic sandpaper. Each time the sandpaper is changed, the sample should be rotated 90 degrees to ensure complete removal of the grinding marks from the previous pass. Before grinding, a layer of glycerin is applied to the sandpaper to prevent abrasive particles from embedding into the sample surface.
[0081] Mechanical polishing includes rough polishing and fine polishing. For rough polishing, use canvas and a 9μm diamond suspension polishing agent. For fine polishing, use velvet and apply 3μm and 1μm diamond suspension polishing agents sequentially. During polishing, apply even pressure to the sample, starting with heavier pressure and gradually decreasing it. Set the polishing disc speed to 300 rpm. In the initial stage of polishing, the direction of the abrasion marks on the sample should be perpendicular to the direction of the polishing disc rotation to facilitate faster removal of the abrasion marks. In the later stages of polishing, rotate the sample slowly.
[0082] b. Add 3.5 mL of hydrochloric acid, 4.5 mL of phosphoric acid, and 92 mL of deionized water to a container in sequence to obtain a metallographic etchant. The mass percentage concentrations of nitric acid and hydrochloric acid used are the same as in Example 1.
[0083] c. Pour the metallographic etchant into a petri dish, place the petri dish in a 25°C constant temperature water bath, immerse the metallographic sample obtained in step a in the metallographic etchant, and etch for 18 seconds. After etching, rinse the sample with anhydrous ethanol and dry it with cold air. Observe the metallographic structure of the Tb diffusion-treated sintered NdFeB permanent magnet alloy under a scanning electron microscope. The morphology after etching is as follows. Figure 5 As shown.
[0084] The composition of the etchant, corrosion time, and corrosion temperature per 100 mL in each embodiment and comparative example are shown in the table below.
[0085] <![CDATA[HNO3]]> HCl <![CDATA[H3PO4]]> <![CDATA[H2O]]> time temperature Example 1 4.5mL 1.5mL 2mL 92mL 18s 25℃ Comparative Example 1 5.5mL 2.5mL / 92mL 18s 25℃ Comparative Example 2 5.5mL / 2.5mL 92mL 18s 25℃ Comparative Example 3 / 3.5mL 4.5mL 92mL 18s 25℃
[0086] from Figure 2 As can be seen from the metallographic etching method of this application, the Tb diffusion-treated sintered NdFeB permanent magnet alloy exhibits clear metallographic grain boundaries, and the (Nd,Tb)2Fe14B shell structure formed by the diffusion process can be clearly observed; from Figure 3 It can be seen that, after Tb diffusion treatment using the metallographic etching method in Comparative Example 1, only obvious grain boundaries can be observed in the sintered NdFeB permanent magnet alloy, but the shell structure cannot be observed; from Figure 4 , 5 It can be seen that the Tb diffusion-treated sintered NdFeB permanent magnet alloys treated by the metallographic corrosion methods in Comparative Examples 2 and 3 can only have some blurry grain boundaries observed, and the shell structure cannot be observed.
[0087] Therefore, the Tb diffusion-treated sintered NdFeB permanent magnet alloy treated by the metallographic etching method of this application shows clear grain boundaries and grains, and a distinct shell structure can be observed. Furthermore, the etching time is short, and the observation is efficient and rapid.
[0088] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.
[0089] In this application, unless otherwise stated, directional terms such as "upper" and "lower" specifically refer to the drawing directions in the accompanying drawings. Furthermore, in the description of this application, terms such as "comprising" and "including" mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this document, "and / or" describes the relationship between related objects, indicating that three relationships can exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone. A and B can be singular or plural. In this document, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c" or "at least one of a, b, and c" can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be a single or multiple.
[0090] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloys, characterized in that, The method includes: The alloy to be tested is pretreated to remove its magnetism and clean it, resulting in a pretreated sample. The alloy to be tested is a Tb diffusion-treated sintered NdFeB permanent magnet alloy formed with Nd2Fe. 14 B crystals form the core, (Nd,Tb)2Fe 14 B represents the core-shell structure of the shell layer, with a Tb content of 1% to 2% by mole fraction. The pretreated sample is thermally mounted to obtain a mounted sample; The inlaid sample is ground and polished to obtain a glossy sample; A corrosive agent is prepared by mixing nitric acid solution, hydrochloric acid solution, and phosphoric acid solution in volume percentages, wherein the nitric acid solution accounts for 4%~5%, the hydrochloric acid solution accounts for 1%~2%, the phosphoric acid solution accounts for 1.5%~2.5%, and the balance is water; the mass percentage concentration of the nitric acid solution is 65%~69%, the mass percentage concentration of the hydrochloric acid solution is 36%~38%, and the mass percentage concentration of the phosphoric acid solution is 83%~90%. The glossy sample was etched using the aforementioned etchant, and then analyzed to observe the (Nd,Tb)₂Fe formed by the Tb diffusion treatment. 14 For the B-shell structure, the corrosion temperature is 22℃~28℃, and the corrosion time is 15~20s.
2. The method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloy according to claim 1, characterized in that, The composition of the alloy to be tested, by mole fraction, includes: neodymium 29%~32.5%; and / or The composition of the alloy to be tested, by mole fraction, includes: 63.95%~68.65% iron; and / or The alloy to be tested, by mole fraction, comprises: 1.1% to 1.2% boron; and / or The composition of the alloy to be tested, by mole fraction, includes: 0.6% to 8% dysprosium; and / or The composition of the alloy to be tested, by mole fraction, includes: 0.3% to 0.5% niobium; and / or The alloy to be tested, by mole fraction, comprises: 0.3% to 0.5% aluminum; The composition of the alloy to be tested, in mole fraction, includes: 0.05% to 0.15% copper.
3. The method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloy according to claim 1, characterized in that, The pretreatment includes demagnetization and cleaning.
4. The method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloy according to claim 1, characterized in that, The heat-mounting process uses HM1 phenolic resin.
5. The method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloy according to claim 1, characterized in that, The grinding sample includes coarse grinding and fine grinding.
6. The method for detecting the core-shell structure of Tb diffusion-treated sintered NdFeB permanent magnet alloy according to claim 1, characterized in that, The polishing sandpaper is at least 800 grit.
Citation Information
Patent Citations
Preparation method of neodymium iron boron metallographic phase
CN107063803A
Metallographic corrosion method and metallographic corrosive agent for aluminum alloy
CN114318341A
